Case Report: Targeting of individual somatic tumor mutations by multipeptide vaccination tailored for HLA class I and II presentation induces strong CD4 and CD8 T-cell responses in a patient with metastatic castration sensitive prostate cancer - Zelba, Henning; Rabsteyn, Armin; Bartsch, Oliver; Kyzirakos, Christina; Kayser, Simone; Seibold, Marcel; Harter, Johannes; Latzer, Pauline; Hadaschik, Dirk; Battke, Florian; Golf, Alexander; Rettig, Matthew B.; et al. (Frontiers in Immunology, 2023)
Localized prostate cancer is curable, but metastatic castration sensitive prostate cancer has a low 5-year survival rate, while broad treatment options are lacking. Here we present an mCSPC patient under remission receiving individualized neoantigen-derived peptide vaccination as recurrence prophylaxis in the setting of an individual treatment attempt. The patient was initially analyzed for somatic tumor mutations and then consecutively treated with two different peptide vaccines over a period of 33 months. The first vaccine contained predicted HLA class I binding peptides only whereas the second vaccine contained both predicted HLA class I and II binding peptides. Intracellular cytokine staining after 12 day in-vitro expansion measuring four T-cell activation markers (IFNg, TNF-α, IL-2, CD154) was used to determine vaccine-induced T-cell responses. While the first vaccine induced only one robust CD4+ T-cell response after 21 vaccinations, co-vaccination of HLA class I and II peptides induced multiple strong and durable CD4+ and CD8+ T-cell responses already after sixth vaccinations. The vaccine-induced immune responses were robust and polyfunctional. PSA remained undetectable for 51 months. The results presented here implicate that neoantigen-targeting vaccines might be considered for those cancer subtypes where therapeutic options are limited. Furthermore, our findings suggest that both HLA class I and II restricted peptides should be considered for future peptide vaccination trials.